Repair of cleft palate: Evolution and current trends - Chona Thomas (Wolters Kluwer Medknow Publications, 2015)
The management of a patient with cleft palate is complex. Various prevalent surgical techniques are presented, but no universal agreement exists on the appropriate treatment strategy. There is a consensus of opinion that normal speech should be the most important consideration in the therapeutic plan. Growth disturbance should be minimized, but not at the expense of speech impairment because facial distortion can be satisfactorily managed by surgery, whereas speech impairment can often be irreversible. There is a need for well-controlled, prospective studies to establish the validity of the widely different claims of superior results from various techniques. Cleft patients should be managed in a center with a multidisciplinary team. Cleft palate remains a significant and interesting challenge for current and future plastic surgeons.